2015
DOI: 10.1007/s10549-015-3501-5
|View full text |Cite
|
Sign up to set email alerts
|

A proposal for a new classification of T4 breast cancer as stage IIIC: a report from the Korean Breast Cancer Society

Abstract: The objective of this study is to investigate staging system of the stage IIIB and stage IIIC Breast cancer and determine the criteria for an update of the classification system. Since AJCC 6th edition, it is pointed out that stage IIIB showed a worse outcome compared with stage IIIC. Using information from two databases, including the nationwide Korean Breast Cancer Registry (KBCR), three cohorts composed of patients from the Asan Medical Center from 1989 to 2002 (cohort I), from 2003 to 2008 (cohort II), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…In the present study, we found that the prognostic difference between stage IIIB and stage IIIC was not differentiated properly according to the anatomic TNM staging. The staging limitation was also described by other studies . Further prognostic evaluation indicated that the survival outcome of T1N3/T2N3 in the stage IIIC was significantly better than T3N3 and T4N3 in the same stage, but not different from that of T4N0 in the stage IIIB.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…In the present study, we found that the prognostic difference between stage IIIB and stage IIIC was not differentiated properly according to the anatomic TNM staging. The staging limitation was also described by other studies . Further prognostic evaluation indicated that the survival outcome of T1N3/T2N3 in the stage IIIC was significantly better than T3N3 and T4N3 in the same stage, but not different from that of T4N0 in the stage IIIB.…”
Section: Discussionsupporting
confidence: 71%
“…The staging limitation was also described by other studies. [24][25][26] Further prognostic evaluation indicated that the survival outcome of T1N3/ T2N3 in the stage IIIC was significantly better than T3N3 and T4N3 in the same stage, but not different from that of T4N0 in the stage IIIB. T4N2 group in the stage IIIB showed a similar prognosis compared with T4N3 in the stage IIIC, but had a worse prognosis than other subgroups in the same stage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Kim et al reported that the survival rate of the IIIB group was lower than that of the IIIC group. A joint analysis of 9640 patients with invasive breast cancer showed that those with stage IIIB disease demonstrated a significantly worse DFS [hazard ratio, HR 10.4; 95% confidence interval (CI) 6.9–15.7] that those with stage IIIC disease (HR 7.2; 95% CI 5.9–8.7) [ 16 ]. Woodward et al yielded similar results, showing a 15-year OS of 18% in stage IIIB disease patients and 28% in stage IIIC disease patients [ 17 ].…”
Section: Discussionmentioning
confidence: 99%